Summary booklet of the global strategy for the conservation and use of Musa genetic resources : A consultative document prepared by the Global Musa Genetic Resources Network (MusaNet) - MusaNet; Chase, R.; Laliberte, B. (Bioversity International, 2016)
This publication summarizes the Global Strategy for the Conservation and Use of Musa Genetic Resources.